PERAN PENGASUH DALAM MENINGKATKAN KEMANDIRIAN ANAK DI PANTI ASUHAN MUHAMMADIYAH CAB.GUGUK II - Nadia Wati, Sri; Syam, Hidayani; Erita, Jhon (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
An orphanage is an institution to shape the development of children who do not have parents or do not live with their families for certain reasons. An orphanage is a house, a place (residence), while or orphanage is a house where you look after and care for orphaned children and so on. In article 55 (33) or Republic or indonesia Law No.23 of 2002, it is explained that in relation to the maintenance and care of abandoned children, government institutions and community institutions, as intended ini paragraph 2, can collaborate with various related parties. An orphanage is defined as a house, place or residence used to care for orphans. In an orphanage, there is a caregiver who will educate, look after, protect and provide comfort to the children in his care. Caregivers are substitute parents who will be respected and appreciated by their foster children. There caregivers play a very important role in increasing the independence of children in the Muhammadiyah Cab.Guguk II orphanage.